Unintended consequences of long-sleeved gowns in a critical care setting during the COVID-19 pandemic. Issue 3 (November 2020) - Meda, M.; Gentry, V.; Reidy, P.; Garner, D.
SUMMARY: At the peak of the coronavirus disease 2019 (COVID-19) pandemic, hand hygiene audits indicated decreased compliance in a 12-bed critical care (CC) area with ventilated COVID-19 patients, where staff used personal protective equipment (PPE), including sessional use of long-sleeved gowns in accordance with the recommendations of Public Health England. There was also a cluster of three central venous catheter (CVC) infections along with increases in the number of patients from whom enteric Gram-negative bacteria (GNB) were isolated from sterile sites. Environmental sampling of near-patient surfaces and frequently touched sites demonstrated that 11.5% of areas were contaminated with enteric GNB in the COVID-19 CC area, compared with 2.6% and 2.7% in COVID-19 and non-COVID-19 general wards, respectively. Following a risk assessment, hospital policy was changed to replace long-sleeved gowns with short-sleeved gowns. The CC unit underwent enhanced cleaning with hypochlorite-based disinfectant and was resampled 8 days later. On resampling, no GNB were isolated from the CC unit. Following this change in PPE, hand hygiene compliance returned to baseline standards and no further CVC infections were identified. Staff reported a preference for short-sleeved gowns. No evidence currently exists that PPE beyond that recommended for pandemic influenza (respiratory protection plus standard PPE) adds to the protection of healthcare workers (HCWs) from severe acute respiratory syndrome coronavirus-2. Long-sleeved gowns prevent HCWs performing hand hygiene effectively. While it is imperative that HCWs are adequately protected, protection of patients from infection hazards is equally important. Further studies are necessary to establish risks from PPE to inform a review of current guidance.